2014
DOI: 10.1186/s40508-014-0025-y
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme promiscuity: using the dark side of enzyme specificity in white biotechnology

Abstract: Enzyme promiscuity can be classified into substrate promiscuity, condition promiscuity and catalytic promiscuity. Enzyme promiscuity results in far larger ranges of organic compounds which can be obtained by biocatalysis. While early examples mostly involved use of lipases, more recent literature shows that catalytic promiscuity occurs more widely and many other classes of enzymes can be used to obtain diverse kinds of molecules. This is of immense relevance in the context of white biotechnology as enzyme cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 87 publications
0
33
0
Order By: Relevance
“…Hydrolases, and in particular lipases, are some of enzymes where catalytic promiscuity has been most extensively studied, as they are able to catalyze a variety of different reactions other than hydrolysis of esters in nonaqueous media, such as transesterification alcoholysis or acidolysis [55]. However, more recently other enzymes have been described to have catalytic promiscuity, including NAD(P)H-dependent oxidoreductases.…”
Section: Specificity and Promiscuity Of Oxidoreductasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrolases, and in particular lipases, are some of enzymes where catalytic promiscuity has been most extensively studied, as they are able to catalyze a variety of different reactions other than hydrolysis of esters in nonaqueous media, such as transesterification alcoholysis or acidolysis [55]. However, more recently other enzymes have been described to have catalytic promiscuity, including NAD(P)H-dependent oxidoreductases.…”
Section: Specificity and Promiscuity Of Oxidoreductasesmentioning
confidence: 99%
“…This indicates that the two enzymes probably had a common ancestor from which they diverged to catalyze consecutive steps of the same metabolic pathway. Substrate promiscuity refers to the property of an enzyme of being able to catalyze the same reaction with a range of different but related substrates [55]. Some are very specific and have just one possible substrate, such as D-hydroxyisovalerate dehydrogenase from the depsipeptide-producing fungus Fusarium sambucinum [58].…”
Section: Specificity and Promiscuity Of Oxidoreductasesmentioning
confidence: 99%
“…The catalytic promiscuity refers to enzymes belonging to a particular class in the enzyme classification (EC) system catalyzing reactions of the type which are generally catalyzed by another class of enzymes. Lipases, classified as hydrolases, have been shown to catalyze many C-C bond formation reactions [10,11,14,15]. It is believed that in such cases, substrates interact with the active site in a manner different from that observed by natural substrates [10].…”
Section: Introductionmentioning
confidence: 99%
“…That still may be the best option but not necessarily the only option. Enzymes can catalyse reactions which are not expected according to their EC classification [46]. For example, recently we showed that a simple lipase can carry out Cannizaro reaction [47].…”
Section: Choosing/tailoring Biocatalystsmentioning
confidence: 99%